Book review – Social Europe: From vision to vigour, Björn Hacker, Brussels, 2023, Publisher: Foundation for European Progressive Studies, ISBN: 978-3-8012-3105-7 - Klára Fóti (Romanian Journal of European Affairs)
This book, authored by Björn Hacker, was published by the Foundation for European Progressive Studies (FEPS), within its Primer Series, in November 2023. It came out well ahead of the European Parliamentary elections – with the obvious purpose of contributing to public debates before the election campaigns. Therefore, its publication was well-timed. Its explicit aim, however, is actually more ambitious: to offer “guidance for those who would like to understand better how social policy at the EU level is made, what are the main tools, who are the most important actors, and when this policy field has been more or less successful in recent decades”.